2006
DOI: 10.1097/01.prs.0000233010.15984.4d
|View full text |Cite
|
Sign up to set email alerts
|

Monobloc Advancement by Distraction Osteogenesis Decreases Morbidity and Relapse

Abstract: Monobloc advancement by distraction osteogenesis had less morbidity and achieved greater advancement with less relapse compared with conventional methods of acute monobloc advancement with bone grafting. Monobloc distraction is superior to conventional methods of acute monobloc advancement and is an alternative to staged fronto-orbital advancement followed by Le Fort III advancement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
112
2
10

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(125 citation statements)
references
References 30 publications
1
112
2
10
Order By: Relevance
“…This is consistent with other published reports. 7,12,51 Our observations are in agreement with those of Bradley et al, 7 who state that there is less morbidity when monobloc advancement is accomplished with distraction osteogenesis than when done in a singlestage surgical procedure; however, Meling et al 38 found no fewer complications. Yonehara et al 60 reported infection around the distracter shaft in 4 of their 19 patients with craniosynostosis treated by distraction osteogenesis.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…This is consistent with other published reports. 7,12,51 Our observations are in agreement with those of Bradley et al, 7 who state that there is less morbidity when monobloc advancement is accomplished with distraction osteogenesis than when done in a singlestage surgical procedure; however, Meling et al 38 found no fewer complications. Yonehara et al 60 reported infection around the distracter shaft in 4 of their 19 patients with craniosynostosis treated by distraction osteogenesis.…”
Section: Discussionsupporting
confidence: 82%
“…The disadvantages of distraction osteogenesis are significant but are heavily outweighed by its many advantages. 1,7,10,22,27 Earlier surgery in many of our patients would, in retrospect, have been better, particularly in those with papilledema. In 20 of the patients in this series, there was convincing evidence of intracranial hypertension, but we did not require the presence of papilledema for this determination.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Type XII (fronto-orbital distraction): there has been an important number of publications in the last decade on suture distraction but they usually include few cases 1,18,34,35 . Something similar occurs with combined fronto-orbital and midface advancement 6,7,10,12,28,31,33 although Cruz et al's series on this regard is outstanding 12 . Recently, Pelo et al 35 reviewed exhaustively the current literature that included 130 cases and added 8 personal instances.…”
Section: Complicationsmentioning
confidence: 99%
“…Other advantages include a reduction in both surgery time and relapse rates. However, patients require further surgery to remove embedded devices following distraction surgery and must wear a halo frame around their head for several months (Bradley et al, 2006).…”
Section: Monobloc Osteotomymentioning
confidence: 99%